Zinc Oxide/Molybdenum Disulfide as Nanocomposite for Multifunctional Sensor Prototype - Netzahualcóyotl Palomera; Peter Feng (Micromachines)
Different materials are studied for environmental gas sensors as well as photodetection prototypes. A ZnO/MoS2 p-n junction was synthetized to act as a multifunctional sensor prototype. After the ZnO was prepared on a silicon substrate by using DC sputtering at room temperature, molybdenum disulfide layers were spin-coated on a nanostructured zinc oxide flake-shaped surface to form an active layer. The heterostructure’s composite surface was examined using scanning electron microscopy, energy-dispersed X-ray, and Raman spectroscopy. Responses to light frequencies, light intensities, and gas chemical tracing were characterized, revealing an enhanced multifunctional performance of the prototype. Characterizations of light-induced photocurrents indicted that the obtained response strength (photocurrent/illumination light power) was up to 0.01 A/W, and the response time was less than 5 ms. In contrast, the gas-sensing measurements showed that its response strength (variation in resistance/original resistance) was up to 3.7% and the response time was down to 150 s when the prototype was exposed to ammonia gas, with the concentration down to 168 ppm. The fabricated prototype appears to have high stability and reproducibility, quick response and recovery times, as well as a high signal-to-noise ratio.